If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(p + -6) = -84 Reorder the terms: 6(-6 + p) = -84 (-6 * 6 + p * 6) = -84 (-36 + 6p) = -84 Solving -36 + 6p = -84 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 6p = -84 + 36 Combine like terms: -36 + 36 = 0 0 + 6p = -84 + 36 6p = -84 + 36 Combine like terms: -84 + 36 = -48 6p = -48 Divide each side by '6'. p = -8 Simplifying p = -8
| 8(3g+2)-3g=3(5g-4)2 | | -5u-u=12 | | 5+r=17 | | 9x-9=x+15 | | 4.3x=11 | | 2y+4.5=11.5 | | 7x-5=2x+19 | | 24+7=38 | | 11x+8x= | | 3(8+7x)=192 | | 9x^3-6x^2-6x+4= | | 12+3p=8p+2 | | 3-8(2x-1)=27 | | 7+13=1 | | (a-bi)(a+i)=0 | | 7x+5-2x+8= | | -9=u-6 | | 4a+6a+8b-5b= | | 3x+7=15-12x | | -3w-(-9)=12 | | P(t)=5t^2+12t+2 | | z/3.5=4 | | 47-11=36 | | 2(12.5-4x)+2x=11.5 | | 9-16y^2=0 | | 42/0.2 | | 5(7a-8)=-320 | | 12z=168 | | 2(12.5-4x)+2y=11.5 | | 4y+2.6y=36 | | 2x+7=x+7+x | | 3x-2sin(x)+7=0 |